(untitled) (Educational Knowledge, 2021)
This article proposes a multidisciplinary approach to the dimensions of human development, emphasizing the need for a comprehensive, holistic, and systemic approach to achieve individual and social fulfillment. The dissertation stems from a literature review that highlights the theoretical, conceptual, and epistemological contributions supporting human development as the purpose of educational and political programs. From this perspective, it concludes that human beings, as a supra-complex system, require the integration of strategic efforts and inclusive policies that promote multifaceted and multidimensional development, enhancing their growth, holistic well-being, and quality of life.